2021
DOI: 10.1039/d1nr01314a
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free exosome-laden scaffolds for tissue repair

Abstract: With the development of regenerative medicine, tissue repair at the molecular, cellular, tissue, and organ level has seen continuous improvements over traditional techniques. As the core of tissue repair, seed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(58 citation statements)
references
References 86 publications
0
58
0
Order By: Relevance
“…Extensive studies have demonstrated the role of exosomes in drug delivery (Duan et al, 2021a;Duan et al, 2021b;Duan et al, 2020b;Huang et al, 2021;Liang et al, 2021a;Xu et al, 2021). Additionally, the limitation of native exosomes in drug delivery has been recognized.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies have demonstrated the role of exosomes in drug delivery (Duan et al, 2021a;Duan et al, 2021b;Duan et al, 2020b;Huang et al, 2021;Liang et al, 2021a;Xu et al, 2021). Additionally, the limitation of native exosomes in drug delivery has been recognized.…”
Section: Discussionmentioning
confidence: 99%
“…The 3D scaffold can be used as a platform for the release of exosomes in the joint tissue repair area [ 69 ]. Exosome-laden 3D materials can be loaded with small molecule compounds, such as miRNAs that are used for drug delivery, and used as cell-free therapeutic products for tissue repair [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…This treatment method has been shown to be more beneficial than a single, direct administration of exosomes due to a slow, steady rate of delivery, with some gels delivering exosomes for up to a week [300][301][302]. These scaffolds offer structure, hydration, and increased flexibility in treatment options, as hydrogels can been used for wounds from basic skin injuries to deep nerve damage [302,303]. In the continued development of wound healing strategies continue, the broad applicability and therapeutic benefits of exosomes will only expand the prospects and efficiency of wound healing technologies.…”
Section: Inflammatorymentioning
confidence: 99%